SIMBOL DAN MAKNA BUDAYA NYAWE? DAN BERAS PATI: UPAYA PEMERTAHANAN BAHASA MASYARAKAT SASAK - Ahmad Sam'un (Center of Language and Cultural Studies, 2017)
This study is aimed to describe meaning represented in symbols of rituals of NyawE and Beras Pati in Sasak society. The study used ethnolinguistics approach, assigning native speakers of Sasak language residing in the city of Mataram. Data were collected using observation, interviews and document analysis. The study revealed that symbols in the tradition are identified in terms of bamboo (terEng) and palm leaf (daon nao) having spiritual meanings for the Sasak society. Nowdays, the symbols have been prevented as the existance of Sasak tribe especially for elderly generation.